2018
DOI: 10.1063/1.5039888
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric memory effect of paramagnetic nonpolar phase in Co4Nb2O9

Abstract: A polarization memory effect of the paramagnetic nonpolar phase is observed in magnetoelectric antiferromagnet Co4Nb2O9, which has a magnetic field induced polarization in the antiferromagnetic phase. Following magnetoelectric poling in the polar phase, the nonpolar paramagnetic state retains a strong memory of polarization. When reentering the polar phase without applying the electric field, a polarization along the initial poling direction is recovered. If the applied magnetic field while staying in the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Previously, similar memory effects have been observed in multiferroic helimagnets [18][19][20][21][22][23][24][25]. Some of these effects are suggested to be caused by the so-called polar nanoregion [18][19][20][21]. In other cases, the charge degree of freedom seems to be responsible for the memory effect [22][23][24].…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Previously, similar memory effects have been observed in multiferroic helimagnets [18][19][20][21][22][23][24][25]. Some of these effects are suggested to be caused by the so-called polar nanoregion [18][19][20][21]. In other cases, the charge degree of freedom seems to be responsible for the memory effect [22][23][24].…”
supporting
confidence: 65%
“…The origin of this memory effect is ascribed to the Bloch-type domain walls in the ferromagnetic state. Previously, similar memory effects have been observed in multiferroic helimagnets [18][19][20][21][22][23][24][25]. Some of these effects are suggested to be caused by the so-called polar nanoregion [18][19][20][21].…”
supporting
confidence: 64%
“…The family of M 4 A 2 O 9 (M = Co, Mn and A = Nb, Tb) compounds was initially reported by Fischer et al [11] to show a similar magnetoelectric coupling under application of a magnetic field below their magnetic ordering temperature. In recent years, several works have been published considering the magnetic, structural, and magnetoelectric features in this series of compounds [9,[12][13][14][15][16][17][18][19][20][21]. Among these compounds, Co 4 Nb 2 O 9 has been reported to show high magnetoelectric coupling at the vicinity of its Néel transition temperature [13,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of the external magnetic field (H = 0), the magnetic structure is collinear (ϕ = 0) and O 1 = 0 in Eq. (13). Therefore, the polarization does no appear.…”
Section: (A) Expectation Values Of the Spin Operators At The Amentioning
confidence: 95%
“…2 Since the reports on a spin-flop driven magneto-dielectric effect 3 and a large magnetoelectric coupling in Co 4 Nb 2 O 9 , 4 this system attracted much attention. [5][6][7][8][9][10][11][12][13] Among them, Khanh and coworkers investigated the linear magnetoelectric effects in detail and found that the electric polarization rotates in the opposite direction at the twice speed relative to the rotation of the external magnetic field applied in the basal ab-plane. 6,9 This point was microscopically studied by Yanagi and coworkers from a band picture under a strong antiferromagnetic (AF) molecular field on the basis of the linear response theory.…”
Section: Introductionmentioning
confidence: 99%